A Call to Action: Evidence for the Military Integration of Teledermoscopy in a Pandemic Era - Gehan A. Pendlebury; John Roman; Vikas Shrivastava; Jerry Yuan (MDPI AG, 2022)
Skin disease remains a common complaint among deployed service members. To mitigate the limited supply of dermatologists in the U.S. Military Health System (MHS), teledermatology has been harnessed as a specialist extender platform, allowing for online consultations in remote deployed settings. Operational teledermatology has played a critical role in reductions of medical evacuations with significant cost-savings. When direct in-person lesion visualization is unattainable, teledermoscopy can be harnessed as an effective diagnostic tool to distinguish suspicious skin lesions. Teledermoscopy has the versatile capacity for streamlined incorporation into the existing asynchronous telemedicine platforms utilized worldwide among deployed U.S. military healthcare providers. In terms of clinical utility, teledermoscopy offers a unique and timely opportunity to improve diagnostic accuracy, early detection rates, and prognostic courses for dermatological conditions. Such improvements will further reduce medical evacuations and time away from mission, thereby operational improving mission readiness and combat effectiveness. As mission goals are safeguarded, associated operational budget costs are also preserved. This innovative, cost-effective technology merits integration into the U.S. Military Health System.